Technology Influences Comics for Education - Hadi, Ariesto (CV TOPAZART, 2023)
Non-fungible tokens (NFTs) are transferrable rights to digital assets, such as art, in-game items, collectibles, or music. The phenomenon and its markets have grown significantly since early 2021. This study aims to find the most popular NFT type. Furthermore, this study aims to describe how technology influences the creation of NFT comics so it is used for education easily. This study uses a qualitative research method. This study uses a qualitative research method focusing on developing NFT comics. Information is collected from journal articles and websites. The research findings show that technology increases the NFT comic industry, especially for education. The main factor is contributing blockchain technology to creators and collectors. In addition, comics help students in reading and writing. They can now use mobile technologies to access the NFT comics and find, read, and write learning.